Effect of scrubbing technique with mild self-etching adhesives on dentin bond strengths and nanoleakage expression - Thanatvarakorn O. (2017)
© Quintessenz. All right reserved. Purpose: To evaluate the effect of a scrubbing technique with one-step self-etching adhesives on bond strengths and nanoleakage expression at the resin/dentin interface. Materials and Methods: Flat human dentin surfaces bonded with one of two mild self-etching adhesives, SE One (SE) or Scotchbond Universal (SU) applied either with scrubbing or without scrubbing technique, were prepared (n = 5). The microtensile bond strengths (μTBS), SE micrographs of morphologica l changes on treated dentin surfaces, and expression of nanoleakage along the bonded dentin interfaces as shown with TEM were evaluated. μTBS data were analyzed using two-way ANOVA and the post-hoc t-test at the significance level of 0.05. Results: The scrubbing technique had a significant positive effect on the μTBS of SU (p < 0.05), while it produced no significant difference for SE (p > 0.05). Morphological evaluation of the treated dentin surfaces demonstrated that SU with scrubbing showed the highest etching ability, followed by scrubbing SE > nonscrubbing SE > nonscrubbing SU. In the nonscrubbing groups, nanoleakage formation using SU exhibited a reticular pattern throughout the hybridized complex, whereas with SE, water-tree nanoleakage was only found in the adhesive layer at dentinal tubule orifices. The scrubbing groups of both adhesives did not exhibit any nanoleakage expression. Conclusion: Using a scrubbing technique when applying mild self-etching adhesives could improve resin monomer infiltration into dentin, chase water on adhesive surfaces, and facilitate smear layer removal.